Public Service Quality in Regional Higher Education Transformation: Comprehensive Evaluation and Optimization Strategies for English Language Programs - Aulia Putri Nur Azmi (Journal of Innovative and Creativity, 2026)
This comprehensive study examines the implementation of Public Service Quality (PSQ) principles in transforming regional higher education services, with specific emphasis on English language learning programs. Employing a sequential explanatory mixed-methods design, this research evaluates service quality dimensions through the adapted SERVQUAL framework and develops evidence-based optimization strategies for enhanced educational service delivery. The investigation was conducted at Tadulako University's English Education Program, examining student expectations versus perceived service quality across five critical dimensions: reliability, assurance, tangibles, empathy, and responsiveness. Quantitative findings reveal substantial gaps between expectations and perceptions, with tangibles demonstrating the most significant deficit (-1.24), followed by reliability (-1.08), responsiveness (-0.95), assurance (-0.76), and empathy (-0.42). Qualitative analysis identified technological infrastructure limitations, insufficient faculty competency in innovative pedagogical approaches, fragmented academic management systems, and rigid organizational culture as primary internal barriers. External constraints include budgetary limitations, regulatory inflexibility, and intensified competition from private institutions. The research proposes a comprehensive transformation framework incorporating citizen-centric governance principles, digital service innovation, stakeholder engagement mechanisms, and continuous quality improvement processes. This study contributes theoretical insights to public service management literature in educational contexts while providing practical implementation roadmaps for regional higher education institutions pursuing service excellence and enhanced student satisfaction.